2007
DOI: 10.1021/jp071393s
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Characterization and Fluorescence Optimization of Polycyclic Polymers

Abstract: A systematic series of polycyclic novel polymers was studied by Raman spectroscopy. The effect of the sequential introduction of polycyclic aromatic ring substituents into the delocalized backbone was examined in relation to the variation of the relative ring breathing and stretching as well as the vinyl stretch frequencies. Replacement of the phenyl units by higher order acene moieties such as naphthyl and anthryl results in a shift of the characteristic stretching frequencies, and analysis of the vinyl stret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 24 publications
3
26
0
Order By: Relevance
“…Thus it is evident that the reduction in the Stokes shift would correspondingly be well correlated with the non-radiative rate. This is as expected as it has been shown that the Stokes shift is well correlated with integrated Raman intensity, and thus can be used as a crude measurement of the vibrational activity of the system [18].…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Thus it is evident that the reduction in the Stokes shift would correspondingly be well correlated with the non-radiative rate. This is as expected as it has been shown that the Stokes shift is well correlated with integrated Raman intensity, and thus can be used as a crude measurement of the vibrational activity of the system [18].…”
Section: Resultssupporting
confidence: 85%
“…This is a clear indication that the dominant change, introduced by the systematic alteration of the p conjugated backbone, is the reduction of the non-radiative rate. This result correlates well with the reduction of the relative Raman intensity and the increase in the fluorescence yield published previously [18]. In order to further explore the tentative relationship suggested through the calculation of the radiative rates using the StricklerBerg equation it was decided to experimentally determine the fluorescence lifetime and compare this to the calculated lifetime.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations